The Influence of MicroRNAs on Mitochondrial Calcium - Jaquenod De Giusti, Carolina; Roman, Barbara; Das, Samarjit (Frontiers in Physiology, 2018)
Abnormal mitochondrial calcium ([Ca2+]m) handling and energy deficiency results in cellular dysfunction and cell death. Recent studies suggest that nuclear-encoded microRNAs (miRNA) are able to translocate in to the mitochondrial compartment, and modulate mitochondrial activities, including [Ca2+]m uptake. Apart from this subset of miRNAs, there are several miRNAs that have been reported to target genes that play a role in maintaining [Ca2+]m levels in the cytoplasm. It is imperative to validate miRNAs that alter [Ca2+]m handling, and thereby alter cellular fate. The focus of this review is to highlight the mitochondrial miRNAs (MitomiRs), and other cytosolic miRNAs that target mRNAs which play an important role in [Ca2+]m handling.